A new method for studying platelets, based upon the low-angle light scattering technique. 2. Application of the method in experimental toxicology and clinical pathology. Issue 5 (2005) - Mindukshev Mindukshev, Igor V. Igor V.; Ermolaeva Ermolaeva, Elena E. Elena E.; Vivulanets Vivulanets, Elena V. Elena V.; Shabanova Shabanova, Elena Yu. Elena Yu.; Petrishchev Petrishchev, Nikolay N. Nikolay N.; Goncharov Goncharov, Nikolay V. Nikolay V.; Jenkins Jenkins, Richard O. Richard O.; Krivchenko Krivchenko, Alexander I. Alexander I.
Abstract : A new method for studying platelets based on low-angle light scattering has been applied to studies in experimental toxicology and clinical pathology, using animal and human platelets. Index EC50 for ADP within control groups was estimated to be in the range of 100–180 nmol l –1 (healthy men, rabbits, rats). The refractory state of platelets was obtained by use ADP or ATP concentrations that just caused platelet activation. The time constant and the half-cycle of the refractory state of platelets were calculated. Kinetic parameters of platelet aggregation at interference of hemostasis (rabbit) and the influence of the age factors on the aggregation indices of platelets (rat) were studied. The method of low-angle light scattering was used as a diagnostic tool in experimental low-level intoxication by organophosphates and for interpretation of the pathogenesis of delayed effects. In human patients with ischemic heart disease or with prosthetic heart valves, significant changes in the functional state of platelets were observed. A model for cooperative binding of receptors with ligands on platelets from pregnant women with preeclampsia was developed.